FUNGSI PENGAWASAN DALAM TINJAUAN PENDIDIKAN ISLAM - Sultan Beddu (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2020)
Supervision is an act or process of controlling activities, values, and determining deviations from the implementation of work in accordance with predetermined plans and standards. In Islam, supervision is not only done by humans but also by God who creates, so it is required to do in accordance with what has been planned in the organization so that what is achieved is a common goal. Supervision is very much needed in an organization / educational institution, as a means of control, whether the organizational structure can run efficiently, and also to find out the results achieved are in accordance with plans and standards or not. Educational supervision is the improvement and development of teaching and learning processes in total, in the sense of improving and developing teacher teaching quality, procurement of facilities that support the smooth teaching and learning process, improving the quality of knowledge and skills of teachers, providing guidance and coaching